The role of investment policy in the development of a green economy - Abishov Mukhammed Sarsenbaevuch (THE INNOVATION ECONOMY, 2026)
This article analyzes the role and importance of investment policy in the development of the concept of a green economy. The necessity of effectively directing investments to ensure sustainable economic growth in the context of environmental problems in Uzbekistan, especially in the Republic of Karakalpakstan, is substantiated. The study conducted an economic analysis based on statistical data for 2020-2024, international experience, and government documents. The results show that investment policy is an important tool for accelerating the green economy.